Association of 5α-reductase inhibitor prescription with immunotherapy efficacy in metastatic renal cell carcinoma: a multicenter retrospective analysis - Lin Yang; Hai Huang; Qiong Wang; Peng Wu; Ke Chen; Weijia Li; Bisheng Cheng; Jilin Wu; Jianghua Yang; WenTai Shangguan; Wenxue Huang; Cunzhen Ma; et al. (Journal for ImmunoTherapy of Cancer)
Background Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of metastatic renal cell carcinoma (mRCC), but response rates remain heterogeneous, and reliable predictive biomarkers are lacking. Recent studies suggest that androgen receptor (AR) signaling plays a role in regulating CD8+ T-cell function, implying that 5α-reductase inhibitors (5-ARIs), which lower androgen activity, could enhance antitumor immunity and improve clinical outcomes in patients receiving immunotherapy. This study retrospectively investigates the impact of a history of 5-ARI use (≥12 months) on the efficacy of ICIs in mRCC.Methods We conducted a multicenter retrospective cohort study of 185 patients with mRCC who received ICIs. Patients were stratified based on their history of 5-ARI use. Baseline characteristics included age, body mass index, International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) risk group, programmed death-ligand 1 (PD-L1) expression levels, tumor stage, and metastasis sites. The primary endpoints were progression-free survival (PFS) and overall survival (OS), analyzed using Cox proportional hazards models. Secondary endpoints included objective response rate (ORR) and disease control rate (DCR). Key immunological insights were gained through single-cell RNA sequencing analysis of tumor samples.Results Patients with a history of 5-ARI use demonstrated improved ORR (59.8% vs 39.8%, p=0.0075) and DCR (87.0% vs 78.7%, p=0.1747) compared with those without. The median PFS and OS were significantly longer in the 5-ARI group, with HRs of 0.64 (95% CI: 0.47 to 0.86, p=0.0085) for PFS and 0.65 (95% CI: 0.47 to 0.90, p=0.0271) for OS. Subgroup analysis further indicated enhanced ICI efficacy with 5-ARI use across age, IMDC risk scores, and PD-L1 expression levels. Single-cell RNA sequencing analysis revealed that 5-ARI treated patients exhibited a reduced presence of regulatory T cells and CD8 T-cell exhaustion (CD8 Tex), and lower programmed cell death protein-1 expression in CD8 Tex cells, suggesting an immunologically favorable modification of the tumor.Conclusion A history of 5-ARI use is associated with improved responses to ICI therapy in mRCC, potentially through AR-related modulation of CD8+ T-cell activity and favorable alterations in the immune microenvironment. These findings support further investigation into androgen-targeted approaches as adjunctive strategies in immunotherapy for RCC.